2008
DOI: 10.1136/bjo.2007.131482
|View full text |Cite
|
Sign up to set email alerts
|

Two different PABPN1 expanded alleles in a Mexican population with oculopharyngeal muscular dystrophy arising from independent founder effects

Abstract: The results of this study suggest that OPMD in the Mexican population is mostly due to (GCG)(11) or (GCG)(9) PABPN1 expanded alleles arising from two independent founder effect mutations. These findings add to the definition of the genetic features of the disease and to the establishment of a probable genotype-phenotype correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…OPMD is an autosomal dominant, late-onset myopathy with a prevalence that varies across different populations. It has been previously shown that there is an increased prevalence of the disease in certain regions which is generally linked to a specific size of the expansion, suggesting a potential founder effect [21][22][23]. Based on our data, we estimate the prevalence of the disease to be at least of 5.65/100,000 habitants in the Canary Islands, which is higher than the prevalence reported in other European regions [16,17].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…OPMD is an autosomal dominant, late-onset myopathy with a prevalence that varies across different populations. It has been previously shown that there is an increased prevalence of the disease in certain regions which is generally linked to a specific size of the expansion, suggesting a potential founder effect [21][22][23]. Based on our data, we estimate the prevalence of the disease to be at least of 5.65/100,000 habitants in the Canary Islands, which is higher than the prevalence reported in other European regions [16,17].…”
Section: Discussionmentioning
confidence: 56%
“…On the contrary, the estimated prevalence in Europe is about 0.5 to 1 case per 100,000 habitants and it is even lower in some regions like the United Kingdom or Scandinavia [16][17][18][19][20]. The most frequent reported pathologic allele contains 13 repetitions, although in some specific populations other alleles predominate and could even have a founder effect [15,[21][22][23][24]. In this sense, it has been suggested that the large prevalence of OPMD in Uruguay could be related with a migratory move from the Canary Islands in the 19th century [22,25].…”
Section: Introductionmentioning
confidence: 99%
“…We then searched the literature trying to find any SNP that is associated with the mutated allele. We found four studies reported the presence of specific SNPs that are associated with the polyAla repeat expansion in OPMD32, 33, 34, 35 (Table S3). There are two major limitations of these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Our patients reported an onset of ptosis at around 40 years, which has also been described in the Mexican population, where the mean age at onset of ptosis was 46.5 years in subjects with the (GCG) 11 (GCA) 3 GCG (or (GCN) 15 ) mutation, compared with 54.7 years in those with the (GCG) 9 or (GCN) 13 mutation. [13] All patients showed signs of external ophthalmoplegia, which was severe in two cases.…”
Section: Discussionmentioning
confidence: 95%
“…In the Mexican population, the possibility of two independent founder effects has been suggested, since the (GCG) 11 (GCA) 3 GCG (or (GCN) 15 ) and (GCG) 9 or (GCN) 13 mutant alleles both occurred in the investigated patients. [13] Interestingly, in the study from Uruguay, one of the patients was an individual from SA who also carried the (GCG) 11 (GCA) 3 GCG (or (GCN) 15 ) mutation, but no further details on this patient are available.…”
Section: Discussionmentioning
confidence: 99%